Integration and co-location of HIV/AIDS, tuberculosis and drug treatment services - Sylla, L.; Bruce, R.D.; Kamarulzaman, A.; Altice, F.L. (2007)
Injection drug use (IDU) plays a critical role in the HIV epidemic in several countries throughout the world. In these countries, injection drug users are at significant risk for both HIV and tuberculosis, and active IDU negatively impacts treatment access, adherence and retention. Comprehensive strategies are therefore needed to effectively deliver preventive, diagnostic and curative services to these complex patient populations. We propose that developing co-located integrated care delivery systems should become the focus of national programmes as they continue to scale-up access to antiretroviral medications for drug users. Existing data suggest that such a programme will expand services for each of these diseases; increase detection of tuberculosis (TB) and HIV; improve medication adherence; increase entry into substance use treatment; decrease the likelihood of adverse drug events; and improve the effectiveness of prevention interventions. Key aspects of integration programmes include: co-location of services convenient to the patient; provision of effective substance use treatment, including pharmacotherapies; cross-training of generalist and specialist care providers; and provision of enhanced monitoring of drug-drug interactions and adverse side effects. Central to implementing this agenda will be fostering the political will to fund infrastructure and service delivery, expanding street-level outreach to IDUs, and training community health workers capable of cost effectively delivering these services. (C) 2007 Elsevier B.V. All rights reserved.